Exploring Corporate Environmental Performance Assessment: A Bibliometric Analysis of Global Research Trends - Wahyudi, Didik; Hanani, Nuhfil; Khusaini, Moh.; Rofiq, Ainur (International Journal of Energy Economics and Policy, 2026)
Environmental performance has become a crucial aspect for companies amid the global climate crisis. This study aims to map the global research landscape on methods for assessing corporate environmental performance using bibliometric analysis. By analyzing Scopus-indexed articles from 2015 to 2025, this study identifies key contributors, conceptual structures, and evolutionary trends in this topic. VOSviewer software was used to perform keyword co-occurrence analysis, visualize trend shifts, and map research themes based on keyword clusters. The five research clusters identified include: 1) The Role of Corporate Environmental Management to Corporate Environmental Performance; (2) Environmental Governance; (3) Environmental Performance Measurement and Assessment; (4) Triple Bottom Line and Corporate Attributes; and (5) Green Innovation. To the best of the author’s knowledge, this study is the first to examine the global literature on environmental performance assessment and map the research landscape into several thematic clusters. Thus, this study provides novelty and theoretical contributions to the insights and advancements of the literature on environmental performance assessment and practical contributions to relevant stakeholders, particularly companies.